Become a Wise Millennial in Respect of Technological Development in an Islamic Perspective - Indriani, Risa Nur; Nurhafizha, Aliya; Erliani, Erlin; Nursyahla, Natasya Putri Sabrina; Aeini, Ani Nur (Talenta Publisher, 2023)
The development of increasingly advanced technology is regretted because it has positive and negative impacts. However, the progress and development of technology does not always have a positive impact, there are some irresponsible individuals who use technology as material to carry out their bad actions. Millennials or young people who live in the era of digitalization and globalization do have big responsibilities and must also have principles in living life in the digitalization era that needs to choose a wise attitude in responding to this technological advancement. Counseling which was held on Tuesday 02 November 2021, took place using via zoom with the theme of counseling